Thermodynamic Analysis Based on the ZL205A Alloy Milling Force Model Study - Jing Cui; Xingquan Shen; Zhijie Xin; Huihu Lu; Yanhao Shi; Xiaobin Huang; Baoyu Sun (Lubricants, 2023)
The ZL205A aluminum alloy is mostly used in automobiles, aircraft, aerospace, and other mechanical components, but now, it focuses on the study of its casting performance, and there is still a lack of research on its cutting performance. In this paper, the milling ZL205A aluminum alloy was milled for testing and simulation analysis. The milling test showed that the impact of the axial cutting depth, radial cutting depth, feed, and cutting speed on the milling force was successively reduced. A thermodynamic analysis model is proposed to evaluate the cutting force and tool design in milling. The model considers the front angle and friction angle of the tool, in which the friction angle is adjusted by the friction coefficient, the variable is the cutting parameter, the constant is fitted through the milling experiment, and the effectiveness of the model is verified to predict the milling force. The pre-grinding test was carried out before the experiment, and the stability of the test was proved by observing the macroscopic shape of the chip and the wear of the cutting edge. The model comprehensively considers the tool angle and quickly calculates the minimum load on the milling cutter based on the optimal geometric parameters, which can be used to optimize the milling cutter structure and provide a theoretical basis for the preparation of ZL205A aluminum alloy mechanical components.